Epigenetic Regulation of miRNA Expression in Malignant Mesothelioma: miRNAs as Biomarkers of Early Diagnosis and Therapy - Tomasetti, Marco; Gaetani, Simona; Monaco, Federica; Neuzil, Jiri; Santarelli, Lory (Frontiers in Oncology, 2019)
Asbestos exposure leads to epigenetic and epigenomic modifications that in association with ROS-induced DNA damage contribute to cancer onset. Few miRNAs epigenetic regulated in MM have been described in literature, and miR-126 is one of them which expression is regulated by epigenetic mechanisms. Asbestos-exposure induces early changes of the miRNAs, which are reversibly expressed as protective species, and their irreversibly reflects the inability of the cells to restore the physiological miRNA levels despite the cessation of carcinogen exposure. Changes in miRNA expression, which results from genetic/epigenetic changes during tumour formation and evolution, can be detected in fluids and used as cancer biomarkers. This article reviews the epigenetic mechanisms involved in miRNA expression in MM, focusing on their role as biomarkers of early diagnosis and therapeutic effects.